Revisiting PIMRS and Curriculum Instruction Management: Evaluation of Principalship in Banda Aceh (Universitas Negeri Semarang, 2022)
This research explored how the principals in Banda Aceh XYZ Schools manage the curriculum and instruction and its relatedness to Principal Instructional Management Rating Scale (PIMRS) (Halinger, 1985). This research has 3 research questions and to answer them, a cross-sectional survey, adapted from PIMRS was used and administered to 186 teachers from local schools there. Research findings indicate that principals of Banda Aceh XYZ school played moderate roles (µ =3.78) in managing curriculum and instruction, and no statistical difference between male and female teachers’ perceptions of principals’ roles in managing curriculum and instruction. The results pointed to the importance of having workshops and policy discussions to improve teaching and parallel understanding of curriculum and instruction for teachers and administrators. Abstrak Penelitian ini mengupas bagaimana kepala sekolah di Sekolah-Sekolah XYZ di Banda Aceh mengatur kurikulum dan pengajaran serta keterkaitannya dengan Principal Instructional Management Rating Scale (PIMRS) (Hallinger, 1985). Penelitian ini menjawab tiga pertanyaan penelitian dengan mengadaptasi PIMRS dalam survei terhadap 186 orang guru di sekolah lokal. Hasil penelitian mengidentifikasikan bahwa kepala-kepala sekolah XYZ di Banda Aceh berperan moderat (sedang) (µ =3.78) dalam mengatur kurikulum dan pengajaran, dan tidak ditemukan perbedaan signifikan antara pendapat guru laki-laki dan perempuan dalam hal peran kepala sekolah mengatur kurikulum dan pengajaran. Selain itu hasil penelitian juga menunjukkan pentingnya pelatihan dan pembahasan kebijakan untuk meningkatkan pengajaran dan pemahaman menyeluruh terhadap kurikulum dan pengajaran bagi guru dan admistrator sekolah.